Cerebrospinal fluid biomarkers of Alzheimer's disease in a cohort of adults with Down syndrome. Issue 1 (9th July 2020) - Henson, Rachel L.; Doran, Eric; Christian, Bradley T.; Handen, Benjamin L.; Klunk, William E.; Lai, Florence; Lee, Joseph H.; Rosas, H. Diana; Schupf, Nicole; Zaman, Shahid H.; Lott, Ira T.; Fagan, Anne M.
Abstract: Introduction: Virtually all individuals with Down syndrome (DS) will develop Alzheimer's disease (AD) pathology by age 40. Cerebrospinal fluid (CSF) biomarkers have characterized AD pathology in cohorts of late‐onset AD (LOAD) and autosomal‐dominant AD (ADAD). Few studies have evaluated such biomarkers in adults with DS. Methods: CSF concentrations of amyloid beta (Aβ)40, Aβ42, tau, phospho‐tau181 (p‐tau), neurofilament light chain (NfL), soluble triggering receptor expressed on myeloid cells 2 (sTREM2), chitinase‐3‐like protein 1 (YKL‐40), alpha synuclein (αSyn), neurogranin (Ng), synaptosomal‐associated protein 25 (SNAP‐25), and visinin‐like protein 1 (VILIP‐1) were assessed in CSF from 44 adults with DS from the Alzheimer's Biomarker Consortium–Down Syndrome study. Biomarker levels were evaluated by cognitive status, age, and apolipoprotein E gene ( APOE ) ε4 carrier status. Results: Biomarker abnormalities indicative of amyloid deposition, tauopathy, neurodegeneration, synaptic dysfunction, and neuroinflammation were associated with increased cognitive impairment. Age and APOE ε4 status influenced some biomarkers. Discussion: The profile of many established and emerging CSF biomarkers of AD in a cohort of adults with DS was similar to that reported in LOAD and ADAD, while some differences were observed.